The 15-minute city as a hybrid model for Milan - Abdelfattah, Lamia; Deponte, Diego; Fossa, Giovanna (TeMA - Journal of Land Use, Mobility and Environment, 2022)
With a special focus on Milan, we explore the interpretation of the 15-minute city as a hybrid model, where soft mobility is integrated in a holistic urbanism approach. Contemporary urban challenges, synthetized in the 15-minute city model, look for a sustainable “proximity mix”: mix of uses (overcoming rigid zoning and building codes), mix of inhabitants and users, mix of time schedules and multi-purpose open space. The proposed hybrid approach considers the living-working urban experience as a whole: it proposes to consider, as a starting point for measuring the timeframe of 15 minutes, not only homes but workplaces as well. It welcomes innovative working facilities among those to be considered as essential services reachable within the 15-minute walking timeframe and it integrates open spaces within urban infrastructures by mixing the neighborhood “eco-system” –both of environment and mobility– and designing them around the central role of walking.